The sensitivity of TIN (IV) oxide thin films at different thicknesses towards CO gas - 419153 Noor Husna Mohd Nayan; Wan Nurulhuda Wan Shamsuri, supervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2008